Potential Threats of Information Disclosure in Social Media: a Systematic Literature Review - Budi Yulianto; Fredy Purnomo; Evaristus Didik Madyatmadja; Meyliana Meyliana; Harjanto Prabowo (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Along with the growth of social media, a variety of potential threats to users is also increasing. These kinds of threats often occur because the users accidentally or unknowingly disclose their information or identity on social media. Threats resulted from the disclosure of information are needed to be known so that the users can understand the risks that arise and take precautions. This research was aimed to summarize the potential threats arising from the information disclosure in social media. The research method used was a systematic literature review to explore and summarize the literatures that discuss the specific topic. The research results show that the potential threats are mostly social threats and identity theft.